2016
DOI: 10.1093/mnras/stw257
|View full text |Cite
|
Sign up to set email alerts
|

Solo dwarfs I: survey introduction and first results for the Sagittarius dwarf irregular galaxy

Abstract: We introduce the Solitary Local Dwarfs Survey (Solo), a wide field photometric study targeting every isolated dwarf galaxy within 3 Mpc of the Milky Way. Solo is based on (u)gi multi-band imaging from CFHT/MegaCam for northern targets, and Magellan/Megacam for southern targets. All galaxies fainter than M V −18 situated beyond the nominal virial radius of the Milky Way and M31 ( 300 kpc) are included in this volume-limited sample, for a total of 42 targets. In addition to reviewing the survey goals and strateg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 117 publications
3
42
0
Order By: Relevance
“…We have checked the literature for evidence of an extended halo in these galaxies but we did not find any paper showing its existence. The only exception is SagDIG, for which we have found a published radial profile (Higgs et al 2016), but it did not show evidence for two stellar components (galaxy and halo) and the galaxy showed a possible signature of tidal stripping.…”
Section: Summary and Discussionmentioning
confidence: 72%
“…We have checked the literature for evidence of an extended halo in these galaxies but we did not find any paper showing its existence. The only exception is SagDIG, for which we have found a published radial profile (Higgs et al 2016), but it did not show evidence for two stellar components (galaxy and halo) and the galaxy showed a possible signature of tidal stripping.…”
Section: Summary and Discussionmentioning
confidence: 72%
“…Making specific predictions will help ensure that the most promising targets are observed to avoid spending significant amounts of telescope time on many (potentially unnecessary) pointings to cover the full virial volume of a given field galaxy. We explicitly calculate expected numbers for galaxies included in the Solo dwarf survey Higgs et al (2016), which has recently observed all isolated dwarf field galaxies within 3 Mpc of the MW. For instance, a single pointing at IC 4662 with their 1 • × 1 • camera would cover a volume that encompasses a mean of ∼ 0.9 − 1.2 satellites with M * > 10 4 M according to the Moster, GK16, and GK14 models.…”
Section: Discussionmentioning
confidence: 99%
“…We apply the same calculations to all of the galaxies in Table 3 using an approximate field of view from the Solo dwarf survey. Solo has a 1 • × 1 • camera (Higgs et al 2016), which we approximate as a circular aperture with radius 0.56 • . We present all of the values expected for Solo in thē N fov column.…”
Section: Survey Strategy: Dependence On Field Of Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…UGC 4879 is presented here as one example of the Solo dwarfs. The basic analysis techniques are detailed in Higgs et al (2016). Fig.…”
Section: Example Galaxy: Ugc 4879mentioning
confidence: 99%